2014
DOI: 10.1097/wnr.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological evidence for the country-of-origin effect

Abstract: Consumers often rely on observable cues that hint at the hidden quality of a product. The aim of this study was to investigate brain activities associated with the country-of-origin (COO) effect and consumer evaluation of a product design. Electroencephalogram recordings were used to observe event-related brain potentials associated with the COO effect and design evaluation. We found that the frontocentral N90 and parieto-occipital P220 amplitudes are involved in forming preference to design, whereas the COO e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The COE effect is defined as the positive or negative influence of the country of origin (country of production) of the product or brand in terms of attitude toward it and probability of buying it (Obermiller and Spangenberg, 1989; Elliott and Cameron, 1994; Verlegh and Steenkamp, 1999). Many researches on the country-of-origin effect have shown that providing consumers with information about the origin of the product or brand influences information processing (Hong and Wyer, 1989; Maheswaran, 1994).…”
Section: Implicit Consumer Ethnocentrism (Ice) Vs Competence Of Counmentioning
confidence: 99%
“…The COE effect is defined as the positive or negative influence of the country of origin (country of production) of the product or brand in terms of attitude toward it and probability of buying it (Obermiller and Spangenberg, 1989; Elliott and Cameron, 1994; Verlegh and Steenkamp, 1999). Many researches on the country-of-origin effect have shown that providing consumers with information about the origin of the product or brand influences information processing (Hong and Wyer, 1989; Maheswaran, 1994).…”
Section: Implicit Consumer Ethnocentrism (Ice) Vs Competence Of Counmentioning
confidence: 99%
“…In our study, we focus on the last of the aforementioned factors. Research on the influence of COO information on product perception shows that it can have both a positive or negative character ( Hong and Wyer, 1989 ; Obermiller and Spangenberg, 1989 ; Liefeld, 1993 ; Elliott and Cameron, 1994 ; Maheswaran, 1994 ; Verlegh and Steenkamp, 1999 ; Hamin and Elliott, 2006 ; Bolliger and Réviron, 2008 ; Koschate-Fischer et al, 2012 ; Rios et al, 2014 ). According to the “made-in” phenomenon, COO information may result in positive (vs. negative) product perceptions when the consumer believes (vs. does not believe) that the country which produced the particular product specializes in manufacturing these types of goods ( Verlegh and Steenkamp, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Functional Emotion Theory, emotions accelerate people’s decision-making and evoke responses [ 45 ]. When presented with stimuli related to a product or brand, the consumer’s brain is highly responsive [ 46 , 47 ]. It captures visual information from the advertisement or product instantly while also retrieving relevant stored memory information for advanced cognitive processing [ 48 ].…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%